2010
DOI: 10.1200/jco.2009.24.7353
|View full text |Cite
|
Sign up to set email alerts
|

Tracheoesophageal Fistula Formation in Patients With Lung Cancer Treated With Chemoradiation and Bevacizumab

Abstract: PURPOSE Tracheoesophageal fistulae are rare complications of thoracic cancers and their treatments. Novel antiangiogenic agents in cancer treatment such as bevacizumab potentially impact wound healing and may contribute to tracheoesophageal fistula development. PATIENTS AND METHODS We conducted two independent phase II clinical trials in small-cell lung cancer and non-small-cell lung cancer using bevacizumab in combination with chemotherapy and radiation. Both trials were intended to assess preliminary efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(144 citation statements)
references
References 16 publications
2
132
1
9
Order By: Relevance
“…However, the development of tracheoesophageal fistulae (Fig. 1) in two phase II trials led to early closure of the trials, U.S. Food and Drug Administration warnings, and a change in the bevacizumab package labeling [53]. Of the 25 patients enrolled in the two trials, suspected or confirmed tracheoesophageal fistulae were observed in five patients.…”
Section: Bevacizumabmentioning
confidence: 99%
“…However, the development of tracheoesophageal fistulae (Fig. 1) in two phase II trials led to early closure of the trials, U.S. Food and Drug Administration warnings, and a change in the bevacizumab package labeling [53]. Of the 25 patients enrolled in the two trials, suspected or confirmed tracheoesophageal fistulae were observed in five patients.…”
Section: Bevacizumabmentioning
confidence: 99%
“…The progression-free and overall survival times were not longer in the overall study population, but in a subgroup analysis, patients with LS-SCLC who received vandetanib (n ϭ 23), versus placebo (n ϭ 23), experienced a longer overall survival time (hazard ratio, 0.45; p ϭ .07). A phase II trial investigated the combination of carboplatin, irinotecan, and bevacizumab in combination with TRT, and that trial was stopped early after two patients developed tracheoesophageal (TE) fistula and a third patient died from an aerodigestive hemorrhage [71]. Of note, the two patients developed TE fistula 2 and 5 months after completion of TRT.…”
Section: Chemotherapy and Targeted Agents In Ls-sclcmentioning
confidence: 99%
“…Intrathoracic cavitation (not necessarily airway necrosis) after bevacizumab has been reported with a median time of 1.8 months (range 0.7-6.2 months) [3]. However case reports identifying airway necrosis and fistula formation, while sparse, appear to be reported in the range of 3 weeks to 10 months after bevacizumab therapy [4,[7][8][9]. The exact mechanism for this spontaneous hemorrhage/perforation remains unclear, but some propose impaired neovascularization and resultant dysfunctional wound healing.…”
Section: Discussionmentioning
confidence: 97%
“…Currently at least four reports have identified seven patients developing airway necrosis and intrathoracic fistula (esophageal, mediastinum, pleura) in the setting of bevacizumab and raditotherapy [4,[7][8][9]. Interesting all these reports involve patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation